Design of Large Poly‐Si on Oxide Interdigitated Back Contact (POLO IBC) Silicon Solar Cells with Local Al–p+ Contacts in the Constraints of Measurement and Module Integration. Issue 11 (23rd September 2022) - Haase, Felix; Hollemann, Christina; Wehmeier, Nadine; Bothe, Karsten; Min, Byungsul; Schulte-Huxel, Henning; Brendel, Rolf; Peibst, Robby
Abstract : Interdigitated back contact (IBC) silicon solar cells with a passivating n‐type poly‐Si on oxide emitter and an aluminum‐doped p + base contact on M2‐sized Ga‐doped p‐type Cz wafers are reported. The Al‐doped base contact forms during the firing of the printed contacts and allows for a lean process flow. The device optimization balances recombination at the base contacts against resistive losses and respects constraints set by the need of interconnecting cells in a module and contacting the cells temporally by a measurement chuck. A special sample holder is designed for measuring the I sc –V oc curve of the IBC cell with a busbar‐less metal grid. The pseudo‐efficiency is 24.7%. All fingers of each polarity are connected with wires and an efficiency of 22.3% is measured. The comparison of simulations and measurements reveals that the cell has 23.4% efficiency without the series resistance losses due to the wires. A huge part of the resistive losses in the cell are the transport losses of the majorities in the base dissipating a power that corresponds to 0.76%abs efficiency and the resistive losses at the Al‐doped base contact (0.29%abs ). Abstract : Busbar‐less M2‐sized p‐type poly‐Si on oxide interdigitated back contact (IBC) cells with Al‐doped base contacts are measured and simulated. A special sample holder is developed for measuring the I sc –V oc curves of busbar‐less IBC cells. An efficiency of 23.4% is analyzed in the current cell. A power loss analysis predicts an efficiency potential of 25%.